Le travail interespèces de pollinisation dans les écologies perturbées - Robin Mugnier (Revue d'anthropologie des connaissances)
For a century, the bee has been put to service as an agriculture’s pollinator. To ensure the crop’s pollination, farmers resort to the pollination service and rent colonies to beekeepers. Based on an ethnographic fieldwork in the Rhone Valley, the article follows conceptions and practices around what the bee's work in pollination should be. It looks at the beekeeper’s activities to prepare colonies for work in intensive agricultural ecosystems. These interspecies pollination practices are performed in "troubled ecologies" (Besky & Blanchette, 2019): agricultural ecosystems in which work and nature present themselves in their fragility. While these ecologies require the service of the bee to remain productive, they offer challenging and delicate conditions to carry out this work, requiring then to increase its load, for the bees as well as for beekeepers.